2008
DOI: 10.1007/s00128-008-9498-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Eight Organophosphorus Pesticide Residues in Fresh Vegetables Retailed in Agricultural Product Markets of Nanjing, China

Abstract: A method to effectively remove pigments in fresh vegetables using activated carbon followed cleanup through solid phase extraction (SPE) cartridge to further reduce matrix interference and contamination, was established to determine eight organophosphorous pesticides (OPPs) by gas chromatography (GC) with nitrogen-phosphorus detection (NPD) in this study, and it has been successfully applied for the determination of eight OPPs in various fresh vegetables with the recoveries ranging from 61.8% to 107%. To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…In total, the pesticide residues that are found in vegetables become a global phenomenon. A similar study reported that, the residue of carbamate pesticides in Potato tuber samples in Egypt and abroad, agrees with this study (Abd El Rahman, 2005;Mansour et al, 2009;Wang et al, 2008;Quinetro et al, 2008).…”
Section: Resultssupporting
confidence: 91%
“…In total, the pesticide residues that are found in vegetables become a global phenomenon. A similar study reported that, the residue of carbamate pesticides in Potato tuber samples in Egypt and abroad, agrees with this study (Abd El Rahman, 2005;Mansour et al, 2009;Wang et al, 2008;Quinetro et al, 2008).…”
Section: Resultssupporting
confidence: 91%
“…These findings indicate that pesticides were extensively used in parsley, lettuce and spinach cultivation in Hatay. Wang et al (2008) analyzed eight organophosphorus pesticide residues (OPP) in fresh vegetables retailed in agricultural product markets of Nanjing (China). While dimethoate (0.118-0.124 mg kg (26.7%), fonofos and fenthion were not detected in any of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The analyses followed published procedures (Rastrelli et al, 2002;Anastassiades et al, 2003;Hamscher et al, 2007;Wang et al, 2008;Lv et al, 2009). In brief, the homogenized lettuce sample (10 g), ethyl acetate (20 g), and anhydrous sodium sulfate (15 g) were mixed thoroughly in a 50-ml centrifuge tube wrapped in silver paper using a vortex mixer, and were shaken for 30 min by reciprocating shakers at room temperature.…”
Section: Validation Of the Methodsmentioning
confidence: 99%